TRPM2 in the Brain: Role in Health and Disease - Giulia Sita; Patrizia Hrelia; Agnese Graziosi; Gloria Ravegnini; Fabiana Morroni (Cells, 2018)
Transient receptor potential (TRP) proteins have been implicated in several cell functions as non-selective cation channels, with about 30 different mammalian TRP channels having been recognized. Among them, TRP-melastatin 2 (TRPM2) is particularly involved in the response to oxidative stress and inflammation, while its activity depends on the presence of intracellular calcium (Ca2+). TRPM2 is involved in several physiological and pathological processes in the brain through the modulation of multiple signaling pathways. The aim of the present review is to provide a brief summary of the current insights of TRPM2 role in health and disease to focalize our attention on future potential neuroprotective strategies.